Qualidade da água de consumo e ações de educação ambiental em escolas do campo de Uberlândia-MG - Medeiros, Maraína Souza (2017)
Water is a limited natural resource which is indispensable to the existence of life on Earth, but its lower quality may bring harmful effects on flora, fauna and biota. In rural areas, specifically, the domestic sewage, animal waste, and agricultural fertilizers and pesticides are the main pollution point sources of water resources (surface and underground springs). In this scenario, schools and farms suffer from the absence of basic sanitation and, therefore, resort to the system of underground water (artesian wells) for purposes of consumption and cleaning. Generally, the only step of treatment of this water is only chlorination and when it is possible. As a result, several problems can happen, including, salutary reduced the academic performance of these children, depending on the consumption of water probably improper. In this sense, this work carried out a diagnosis of the water quality intended for human consumption and also that used in meals preparation of students in three rural schools of Uberlandia-MG. In addition, the conditions were evaluated sanitary hygienic catchment system, storage, and distribution used by checking its relationship with water quality. As for the diagnosis of water quality samples were collected in four different sampling points, since the storage system to the distribution and consumption of water. These samples were analyzed physical parameters (color, turbidity, electrical conductivity and temperature), chemical (pH, total dissolved solids, salinity, total hardness, total iron, total organic carbon and residual chlorine) and microbiological (e. coli) for determining the water quality supplied in schools. Finally, pedagogical strategies on water have been prepared and applied (importance, waste in everyday activities, pollution and contamination, and water-borne diseases), based on the target audience-school age, in order to enhance the environmental awareness of the local community. The educational activities were developed in an interactive way with learners, giving emphasis to the action research of the participant character, promoting the exchange of scientific knowledge by environmental educators with common sense knowledge of students. Thus, the analytical data obtained were confronted with the current legislation (Ordinance No. 2,914/2011, 357 of CONAMA Resolution 2005, and Resolution 396 of 2008, CONAMA) and thus was found if the water supplied in schools are fit for human consumption. In addition, the didactic activities of EE used aimed at obtaining a greater environmental awareness of students who lived in the rural localities.